Combating tax aggressiveness: Evidence from Indonesia's tax amnesty program - Muhammad Arsalan Khan; Siti Nuryanah (Cogent Economics & Finance, 2023)
Taxation has a vital role as a domestic financial source to achieve Sustainable Development Goals (SDGs). To increase domestic revenue, combating tax avoidance is important, especially for Indonesia, one of the most populous countries with the fact that the 2020 country's tax-to-GDP ratio decreased to 10.1% in 2020 which is below the Asia and Pacific average of 19.1%. This paper examines the effect of the tax policy of Indonesia, i.e., tax amnesty and other factors on tax aggressiveness. Indonesia is taken as the case study for the specific characteristics of its tax reforms. The sample of this study consists of 402 observations from manufacturing companies listed in the Indonesian Stock Exchange (IDX) for the periods of 2013-2018. This study collected secondary data and employed a purposive sampling method for the selection of samples. Multiple regression analysis was used to examine the factors affecting tax aggressiveness. The results show that internal governance mechanisms, namely independent commissioners and institutional ownership, as well as the company's characteristics, namely leverage and profitability, have a significant effect on tax aggressiveness. This study, however, cannot find the effectiveness of tax amnesty in combatting tax aggressiveness. This study brings an implication for developing tax policies for companies in Indonesia, to reduce tax aggressiveness.
Keywords: 330; effective tax rate; manufacturing companies; Tax aggressiveness; tax amnesty; tax avoidance